Autonomous drone for delay-tolerant networks in indoor applications - Radosław O Schoeneich; Marcin Golański; Bartosz Krok; Paweł Czermiński (International Journal of Distributed Sensor Networks)
This article presents the idea and application of autonomous drones as mobile message ferries in delay-tolerant networks. The delay-tolerant network communication bases on messages ferrying called store-carry-forward paradigm. The messages ferrying can be realized by drones—an autonomous flying robots. For indoor application, drones are equipped with the sensors for distance and obstacle detection. The use of drones can be particularly effective in emergency scenarios where the human-rescuers’ activity is impossible due to hard unhealthy conditions. Our solution was tested in indoor scenario. The test results demonstrate good performance of our solution.